Alginate–marine collagen–agarose composite hydrogels as matrices for biomimetic 3D cell spheroid formation. Issue 52 (12th May 2016) - Shin, Suil; Ikram, Muhammad; Subhan, Fazli; Kang, Hae Yeong; Lim, Yeseon; Lee, Rira; Jin, Songwan; Jeong, Young Hun; Kwak, Jong-Young; Na, Yong-Jin; Yoon, Sik
Abstract : We report a novel, customizable, transparent, biocompatible, functional, easy-to-produce, efficient and cost-effective AmCA scaffold for 3D cell culture. Abstract : Hydrogels are prototypical matrices for 3D cell culture, of which alginate hydrogels are extensively used. However, ionic crosslinking agents, such as Ca 2+, are required to form alginate hydrogels, but introduce Ca 2+ -associated cytotoxicity and long-term stability issues. Collagen is a promising biomaterial for 3D cell culture scaffolds primarily due to its biocompatibility. In the present study, the authors designed and fabricated a calcium-free, physically crosslinked, efficient, and bioactive hydrogel composed of alginate, marine collagen, and agarose (AmCA) for use in 3D cell cultures. This AmCA hydrogel was assessed by FTIR, swelling property, scanning electron microscopy, phase contrast microscopy, cell proliferation, cell viability, confocal microscopy, transparency and RT-PCR analyses. The gel was found to exhibit excellent cytocompatibility with various tumor and non-tumor cells, to generate high yields of multicellular spheroids, and to promote cellular activity. Furthermore, the transparency of the AmCA hydrogel suggests it can be used without cell-tracking chemicals in morphological studies of cell cultures. Taken together, it would appear that the described physically crosslinked AmCA hydrogel could provide a novel platform for the development of customizable, transparent, biocompatible, functional, easy-to-produce, and cost-effective scaffolds for use in 3D cultures of various cell types.